PENGUATAN TRADISI AMALIAH NU DI LAKMUD PKPT IPNU IPPNU IAI IBRAHIMY GENTENG BANYUWANGI - Mashuri, Imam; Fauzi, Anis; Nasrodin, Nasrodin (LPPM Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2023)
The Young Cadre Training (Lakmud) is the second phase for NU cadres under the auspices of the IPNU autonomous body IPPNU to create militant cadres. One of the materials provided was the tradition and amaliah Nu in order to strengthen the tradition of Ahlu Sunnah Wal Ja'ma'ah An-Nahdliyyah. NU traditions and practices are the characteristics of NU citizens that must be maintained and preserved for NU citizens in particular and Muslims in general.